Análisis de los resultados socio-económicos obtenidos por asignación de recursos del Sistema General de Regalías en el municipio de Puerto Gaitán durante el periodo 2012-2016 (2017)
This study analyzes the results obtained by the allocation of royalties resources in the municipality of Puerto Gaitán since the entry into force of the new Sistema General de Regalías (SGR) in 2012 until 2016. Through a socioeconomic characterization of the municipality and the study of the development plans and projects financed by the SGR some indicative variables of economic and social development are selected and submitted for analysis. Finally it is found that the health and education coverage is favorable but the allocations have not managed to close the existing gaps between the urban and rural areas. The greatest needs are concentrated in the public services sector, basic sanitation and road infrastructure.